Efeito de campos magnéticos estáticos em irradiação por elétrons - Matheus Corrêa Dantas Avelar (2021)
The present work deals with electron radiotherapy coupled with high external static magnetic fields and the biological response of cells to these. The objective was to determine the relevance of the coupling of external magnetic fields and radioactive beams as an optimization tool in the treatment of tumors. The methodology involved mathematical studies of electron transport and energy deposition as a function of the magnetic field, experimental studies in vitro and computational studies based on the EGSnrc particle transport code. A mathematical model based on the BetheBloch equation was developed to theoretically estimate the energy loss of electrons in matter, when subjected to external magnetic fields. The model was improved with the creation of an algorithm based on the Continuous Slowing Down Approximation (CSDA) method on the real trajectory of a single charged particle under the action of external magnetic fields. Adjacent to the theoretical models, experiments were started seeking to observe the effect of external magnetic fields on breast cancer adenocarcinoma cells, MDAMB231. However, the experiments were stopped before the end. Monte Carlo simulations with the EGSnrc code continued the studies. The experimental findings showed changes in the clonogenicity of the cells, with a significant increase in cell viability when subjected to a static field of 15 Tesla. Theoretical analysis of the path of electrons in magnetic fields showed a reduction in beam range; increased energy deposition; and significant changes in the profiles of indepth and offaxis doses. It was concluded that the various changes, especially regarding energy deposition and reach, present perspectives due to the possibility of shaping the dose profile according to the need, with the use of an external magnetic field. To determine the clinical relevance, simulations should be sought in more complex algorithms that simulate the living tissue and with the addition of more conjugated fields of radiation, as in a real situation.